Fine-scale genetic structure and wolbachia infection of aedes albopictus (Diptera: Culicidae) in Nanjing city, China - Zhang, Heng-Duan; Gao, Jian; Xing, Dan; Guo, Xiao-Xia; Li, Chun-Xiao; Dong, Yan-De; Zheng, Zhong; Ma, Zu; Wu, Zhi-Ming; Zhu, Xiao-Juan; Zhao, Ming-Hui; Liu, Qin-Mei; et al. (Frontiers in Genetics, 2022)
Background:Aedes albopictus is an indigenous primary vector of dengue and Zika viruses in China. Wolbachia is a gram-negative and common intracellular bacteria, which is maternally inherited endosymbionts and could expand their propagation in host populations by means of various manipulations. Compared with research on the dispersion of Ae. albopictus at the macrospatial level (mainly at the country or continent level), little is known about its variation and Wolbachia infection at the microspatial level, which is essential for its management. Meanwhile, no local cases of dengue fever have been recorded in the history of Nanjing, which implies that few adulticides have been applied in the city. Thus, the present study examines how the Ae. albopictus population varies and the Wolbachia infection status of each population among microspatial regions of Nanjing City. Methods: The genetic structure of 17 Aedes albopictus populations collected from urban, urban fringe, and rural regions of Nanjing City was investigated based on 9 microsatellite loci and the mitochondrial coxI gene. The Wolbachia infection status of each population was also assessed with Wolbachia A- and Wolbachia B-specific primers. Results: Nine out of 58 tested pairs of microsatellite markers were highly polymorphic, with a mean PIC value of 0.560, and these markers were therefore chosen for microsatellite genotyping analysis. The Na value of each Ae. albopictus population was very high, and the urban area populations (7.353 ± 4.975) showed a lower mean value than the urban fringe region populations (7.866 ± 5.010). A total of 19 coxI haplotypes were observed among 329 Ae. albopictus individuals via haplotype genotyping, with the highest diversity observed among the urban fringe Ae. albopictus populations (Hd = 0.456) and the lowest among the urban populations (Hd = 0.277). Each Ae. albopictus population showed significant departure from HWE, and significant population expansion was observed in only three populations from the urban (ZSL), urban fringe (HAJY), and rural areas (HSZY) (p < 0.05). Combined with DAPC analysis, all the Ae. albopictus populations were adequately allocated to two clades with significant genetic differences according to population structure analysis, and the best K value was equal to two. AMOVA results showed that most (96.18%) of the genetic variation detected in Ae. albopictus occurred within individuals (FIT = 0.22238, p < 0.0001), while no significant positive correlation was observed via isolation by distance (IBD) analysis (R2 = 0.03262, p = 0.584). The TCS network of all haplotypes showed that haplotype 1 (H1) and haplotype 4 (H4) were the most frequent haplotypes among all populations, and the haplotype frequency significantly increased from urban regions (36.84%) to rural regions (68.42%). Frequent migration was observed among Ae. albopictus populations from rural to urban regions via the urban fringe region, with four direct migration routes between rural and urban regions. Furthermore, Wolbachia genotyping results showed that most of the individuals of each population were coinfected with Wolbachia A and Wolbachia B. The independent infection rate of Wolbachia A was slightly higher than that of Wolbachia B, and no significant differences were observed among different regions. Conclusion: In the microspatial environment of Nanjing City, the urban fringe region is an important region for the dispersion of Ae. albopictus populations between rural and urban areas, and Wolbachia A and Wolbachia B coinfection is the most common Wolbachia infection status in all Ae. albopictus populations among different regions.